Pengaruh Harga Saham, Earning Per Share, dan Sales Growth terhadap Profitabilitas pada Perusahaan Industri Tekstil - Dariana, Dariana; Azizah, Nurul; Nirwana, Ema; MZ, Irawan Fahrudin (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research was conducted with the aim of determining the effect of share price and earnings per share on profitability with sales growth as a moderating variable in textile industry companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. This type of research is quantitative research using the SmartPLS V.4.1.0.0 analysis tool, with a population of 30 companies. Using a purposive sampling technique, the total sample size was 8 samples. The results of this research are that there is a significant influence between share prices and profitability and there is a significant influence between earnings per share and profitability.What differentiates this research from previous research is that it uses the PLS-SEM approach and the SmartPLS V.4.1.0.0 testing tool.This research can help investors who will invest their capital in textile industry companies and for issuers it can be used as material for consideration in making policies regarding profitability.